Asset-building and social inclusion: A qualitative analysis of families' perspectives. (March 2021) - Feldman, Guy
Summary: Social inclusion has historically been one of the key goals of the welfare state. Over the past two decades, an increasing number of policies have aimed to promote inclusion by connecting low-income families to mainstream financial services and enabling them to save and acquire assets. Building on the concept of the "paradox of inclusion, " this article examines whether and how policies that aim to include low-income families in asset accumulation do so in ways that risk reinforcing their exclusion. The article focuses on a case study of a matched savings program in the heart of a major American city, gathering evidence through in-depth interviews with 24 clients in the program and ethnographic observations at the agency implementing the program. Findings: Findings show that the program enhances families' feelings of social inclusion, but it also creates the possibility for social exclusion in two distinctive ways: teaching families to save even under challenging circumstances and encouraging them to pursue the risky venture of homeownership. Application: This research suggests that addressing the structural sources of poverty and training social workers to be more sensitive to low-income families' distinctive circumstances are necessary to ensure that they are included as full members of society.